Penyuluhan Tentang Pentingnya Sistem Antrean Online Menggunakan Aplikasi Mobile JKN Pada Pasien Rawat Jalan BPJS Dirumah Sakit Mitra Sejati Tahun 2025 - Diah Karlina; Ratih Widya Wati Gultom (STIKES Columbia Asia Medan, 2025)
This community service activity aimed to improve administrative staff’s knowledge regarding the importance of the online queue system using the Mobile JKN Application for BPJS outpatient services at Mitra Sejati General Hospital in 2025. The method used was a quasi-experimental design with a pretest–posttest approach involving the entire population of 55 respondents selected through total sampling. The intervention was conducted through direct counseling and assistance. Data were analyzed using the Wilcoxon test with a significance level of α=0.05. The results showed an increase in good knowledge from 63.6% to 76.4% after the intervention, with a p-value of 0.035, indicating a significant difference before and after counseling. The implementation of the Mobile JKN online queue feature proved effective in reducing waiting times, increasing service transparency, and improving patient satisfaction. It is recommended that the hospital continue socialization efforts and encourage optimal use of the application to enhance healthcare service quality.